2013
DOI: 10.1016/j.molcel.2013.08.019
|View full text |Cite
|
Sign up to set email alerts
|

TORC2 Signaling Pathway Guarantees Genome Stability in the Face of DNA Strand Breaks

Abstract: A chemicogenetic screen was performed in budding yeast mutants that have a weakened replication stress response. This identified an inhibitor of target of rapamycin (TOR) complexes 1 and 2 that selectively enhances the sensitivity of sgs1Δ cells to hydroxyurea and camptothecin. More importantly, the inhibitor has strong synthetic lethality in combination with either the break-inducing antibiotic Zeocin or ionizing radiation, independent of the strain background. Lethality correlates with a rapid fragmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 53 publications
4
85
0
1
Order By: Relevance
“…This might be due to our strategy of inducing mutations rather than selecting spontaneously resistant clones. Multiple mutagenesis experiments in fungi and mammalian cells have revealed that there is a bias towards chromosomal aberrations and SNPs in pleiotropic drug-resistance genes if spontaneous mutants are selected and sequenced (Nyfeler et al, 2012;Richie et al, 2013;Sadlish et al, 2013;Shimada et al, 2013). The underlying mechanism might be that amino acid mutations in the essential, primary target can often be deleterious, and these cells are rapidly outcompeted.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to our strategy of inducing mutations rather than selecting spontaneously resistant clones. Multiple mutagenesis experiments in fungi and mammalian cells have revealed that there is a bias towards chromosomal aberrations and SNPs in pleiotropic drug-resistance genes if spontaneous mutants are selected and sequenced (Nyfeler et al, 2012;Richie et al, 2013;Sadlish et al, 2013;Shimada et al, 2013). The underlying mechanism might be that amino acid mutations in the essential, primary target can often be deleterious, and these cells are rapidly outcompeted.…”
Section: Discussionmentioning
confidence: 99%
“…50 and data not shown). Recently, we identified BHS345 as a specific inhibitor of TORC1 and TORC2 both in vitro and in yeast (51). BHS345 is structurally similar to BEZ235 (Fig.…”
Section: Bhs345 Specifically Inhibits Torc1 and Torc2 In Yeast-mentioning
confidence: 96%
“…Recently, we have showed that TORC2 is required under DNA replication stress and for maintenance of telomere length and gene silencing (12). Interestingly, a role for TORC2 in maintenance of genome stability has also been reported in Saccharomyces cerevisiae (13), suggesting that the role of TORC2 in tolerance to DNA damage and genome integrity is conserved in evolution.…”
Section: Target Of Rapamycin (Tor)mentioning
confidence: 97%